2022
DOI: 10.3390/plants11020188
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Molecular Indicators of Plant Virus Infection: Are Plants Able to Tell Us They Are Infected?

Abstract: To our knowledge, there are no reports that demonstrate the use of host molecular markers for the purpose of detecting generic plant virus infection. Two approaches involving molecular indicators of virus infection in the model plant Arabidopsis thaliana were examined: the accumulation of small RNAs (sRNAs) using a microfluidics-based method (Bioanalyzer); and the transcript accumulation of virus-response related host plant genes, suppressor of gene silencing 3 (AtSGS3) and calcium-dependent protein kinase 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…It would be interesting to explore whether the reduction of CPK3 diffusion observed upon PlAMV infection is specific to this virus or if it can be extended to other viral species, genera and even pathogens. Indeed, it was recently shown that CPK3 transcription enhanced upon infection by viruses from different genera 54 . Moreover, CPK3 regulates herbivore responses by phosphorylating transcription factors 20 , is activated by flg22 in protoplasts 19 and is proposed to be the target of a bacterial effector to disrupt immune response 21 .…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to explore whether the reduction of CPK3 diffusion observed upon PlAMV infection is specific to this virus or if it can be extended to other viral species, genera and even pathogens. Indeed, it was recently shown that CPK3 transcription enhanced upon infection by viruses from different genera 54 . Moreover, CPK3 regulates herbivore responses by phosphorylating transcription factors 20 , is activated by flg22 in protoplasts 19 and is proposed to be the target of a bacterial effector to disrupt immune response 21 .…”
Section: Discussionmentioning
confidence: 99%
“…But the sensitivities of these methods cannot meet the need during the latent period of EB (Leiminger, 2009;Latorse et al, 2010;Khan et al, 2018). Because of a lack of proper transcript information that is stably expressed at a high level under a wide range of conditions, it is difficult to ensure the specificity and sensitivity of RNA-based assays (Di Gaspero et al, 2022;Valmonte-Cortes et al, 2022). So, RNA-based methods have not been adopted in past studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the same researchers show further that the infection of Arabidopsis with plantago asiatica mosaic virus induced CPK3-dependent increase of REM1.2 diffusion in the PM, which affected the spread of infection ( Jolivet et al , 2023 ). Notably, the accumulation of AtCPK3 transcripts is significantly increased in response to various viral infections ( Valmonte-Cortes et al , 2022 ), further suggesting an important role of CPK3 in antiviral response regulation. Remorin-related regulation of cell-to-cell transport has also been shown for TuMV.…”
Section: Organelle-specific Regulation Of Ca 2+ Si...mentioning
confidence: 99%